Students and Graduation: Procrastination and Academic Achievement - Octavianus, Philia; Banik, Lodia; Nubatonis, Sonia; Boymau, Early (Educationist: Journal of Educational and Cultural Studies, 2022)
Academic procrastination that occurred within the Kupang State Christian Institute (IAKN) for the last three years from 2018 to 2020, the total percentage who reported completing their studies was only around 50% (Source: IAKN Kupang, 2021). The purpose of the study was to determine the impact of academic procrastination on academic achievement in IAKN Kupang students. When students have a tendency to always or almost always postpone assignments and always or almost always experience problematic anxiety associated with procrastination both internally such as subjective and external discomfort such as decreased learning, lost opportunities, health risks, and poor relationships, it will have an impact on procrastinating behavior. The research subjects were 101 students from various study programs, namely pastoral counseling, ecclesiastical music, and Christian religious education who had not completed their study period of 4 years. Collecting data using a closed questionnaire with 5-scale answers. Using the Academic Procrastination Scale-Short (APS-S) measuring instrument which has been developed by Yockey (2016). The measuring instrument test uses the Cronbach alpha validity and reliability test research hypotheses were tested using the technique of moderating regression analysis (MRA). The results showed that there was an impact of academic procrastination on academic achievement (R= 0.560 p<0.05). Further research can use moderator variables such as demographics, in addition to research on personality and well-being variables to see the impact of academic procrastination.